Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
I think that the first part would be -252, but I'm not sure about the second part
Step-by-step explanation:
Find p(–4) if p(x) = 3x^3 – 2x^2 + 6x – 4
p(-4) = 3x^3 – 2x^2 + 6x – 4
p(-4) = 3(-4)^3 – 2(-4)^2 + 6(-4) – 4
= 3(-64) - 2(16) + 6(-4) - 4
= -192 - 32 - 24 - 4
p(-4) = -252
r(x) = x^3 – 2x + 1, find r(2a^3)
r(x) = (x^3 – 2x + 1) (2a^3)
= (2a^3) x^3 + (2a^3) (-2x) + (2a^3) * 1
= x^3 (2a^3) - 2x (2a^3) + 1 * (2a^3)
r(x) = 2a^3x^3 - 4a^3x + 2a^3
I’m not entirely sure about this one as I’m also in 11th grade but I think this is how it’s done.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.